(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
Background: Globally, over 5.2 million children under five years perished in 2019, primarily from preventable causes, with road traffic injuries ranking second among 5–14-year-olds in India in 2000. Injury and violence account for nearly 950,000 annual deaths in those under 18, with unintentional events comprising 90 percent. This study characterizes demographic, epidemiological, and medicolegal features of pediatric and adolescent fatalities in Indore. Material and Methods: In this prospective, one-year investigation (October 2022–September 2023) at Mahatma Gandhi Memorial Medical College, all medico-legal autopsies for individuals ≤18 years were reviewed. Data—drawn from police reports, family interviews, and autopsy findings—were recorded on structured proformas. Cases were stratified by age: infants (≤1 year), toddlers (2–3 years), preschool (4–6 years), school aged (7–12 years), and adolescents (13–18 years). Analyses encompassed age, sex, manner, and mode of death. Results: Of 2,423 autopsies, 120 (4.95 percent) involved ≤18 years. Adolescents predominated (64.2 percent), followed by preschoolers (10.8 percent), school-aged (9.2 percent), toddlers (8.3 percent), and infants (7.5 percent). Males outnumbered females (M: F = 1.5:1), especially in older age groups. Unintentional deaths accounted for 62.5 percent, suicides 26.7 percent, homicides 3.3 percent, natural 2.5 percent, and undetermined 5 percent. Road traffic accidents were the leading mechanism (28.3 percent), followed by poisoning (15.8 percent), asphyxia (13.3 percent), falls (11.7 percent), burns (8.3 percent), and electrocution (4.2 percent). Conclusion: In this Central Indian cohort, adolescents—particularly males—bear the highest burden of fatal injuries. Road traffic collisions and intentional self-harm are predominant. Prevention strategies should emphasize strict traffic enforcement, parental supervision during play, and accessible mental health resources.